M&A Efficiency Islamic Bank Pre-Merger Analysis: Does Control Covid-19 Matter? - Sri Yayu Ninglasari; Nisful Laila; M. Fikri Himmawan (Jurnal Ilmiah Ekonomi Islam, 2023)
Analysis of pre-mergers is important to do as an effort for Islamic banks to increase competitiveness. This study aims to analyze the determinants of the efficiency of pre-merger Islamic banking in Indonesia. This study uses a quantitative research design through the two-stage banking data envelopment analysis (DEA) model. The input variables for the first stage are third party funds (DPK), operational costs (BIOP), total financing (TFIN), and the output variables are operating income (PENDOP), total assets (TASSET). Then in the second stage with multivariate tobit regression, using the dependent variable the efficiency score obtained through the results of the first stage and in the first model the independent variables are total assets, bank size, ROA, NPF, CAR and then measurements are made on additional Covid-19 controls for the second model. The results showed that total assets, bank size, ROA, and CAR significantly affected efficiency scores. NPF has no significant effect. The second model with the Covid-19 control variable produced a more substantial empirical model influence than non-control Covid-19. Overall, the performance of Islamic commercial banks increased until the fourth quarter of 2020, seen from the improving quality of financing, which was also marked by the decline in NPF and quite good intermediation. Limitations of this study include the limited update of the Covid-19 control data.